KINERJA KELEMBAGAAN KELOMPOK TANI HUTAN PEMEGANG IZIN PERHUTANAN SOSIAL DI WILAYAH KELOLA KESATUAN PENGELOLAAN HUTAN KAYUTANGI - Istiqomah Istiqomah; Udiansyah Udiansyah; Hamdani Fauzi (Universitas Lambung Mangkurat, 2021)
The objectives of this research was to identified the Forest Farmer Group’s (KTH) Institutional performance as a holder of social forestry permits and to analyze the factors in the Kayutangi Management Unit (KPH). The method used is the sampling snowballs. Snowball sampling is a technique of sampling data sources, which are small in number at first, and over time become large. Analysis of the Institutional Performance of Forest Farmer Group’s (KTH) MPG Suka Maju and the factors that influence the Institutional Forest Farmer Group’s (KTH) MPG Suka Maju. The results of the institutional performance of Forest Farmer Group’s (KTH) MPG Suka Maju as a social forestry permit holder in the Kayutangi Management Unit (KPH) based on the five components of the field (Location Conditions, Institutions, Group Activities, Impact of Group Activities, and Group Achievements). Forest Farmer Group’s (KTH) MPG Suka Maju is categorized as a Forest Farmer Group’s (KTH) quality class